Species Identification in the Rhododendron vernicosum–R. decorum Species Complex (Ericaceae) - Mao, Xingxing; Wang, Ji; Shrestha, Nawal; Ma, Yazhen; Liu, Jianquan (Frontiers in Plant Science, 2021)
Delimitating species boundaries is the primary aim of biological classification and could be critical for evaluating the evolving process of species and conserving biodiversity. Rhododendron is an iconic group with an extraordinary diversity in southwest China. However, it remains unknown whether the recorded species therein comprise independently evolving lineages or artificially delimitated morphological entities. In this study, we carried out species delimitation of four Rhododendron species in the R. vernicosum-R. decorum species complex based on morphological analyses and population genetic data from nuclear simple sequence repeats (SSR) markers. We randomly selected a total of 105 specimens of different individuals identified as four species across their distributional ranges to examine the statistically distinct phenotypic clusters based on 19 morphological traits. Similarly, we genotyped 55 individuals of four species from 21 populations using 14 SSR markers. The morphological analyses sorted R. decorum and the other three species into two different phenotypic clusters. The genetic clusters were consistent with the morphological clusters. However, we also recovered the third genetic cluster, comprising six R. vernicosum populations and containing the admixed genetic compositions of the other two distinct genetic clusters. This hybrid group was morphologically similar to the typical R. vernicosum (including the samples from its type specimen locality and both R. verruciferum and R. gonggashanense) but with more genetic ancestry from R. decorum. Based on our findings, we identify two distinct species and one putative hybrid group due to introgression in the R. vernicosum-R. decorum species complex. We propose to merge R. verruciferum and R. gonggashanense into R. vernicosum based on genetic compositions and our morphological analyses. The inferred hybrid group inferred from our findings, however, needs further investigations.